Mammography screening reduces rates of advanced and fatal breast cancers: Results in 549,091 women - Duffy, Stephen W.; Tabár, László; Yen, Amy Ming‐Fang; Dean, Peter B.; Smith, Robert A.; Jonsson, Håkan; Törnberg, Sven; Chen, Sam Li‐Sheng; Chiu, Sherry Yueh‐Hsia; Fann, Jean Ching‐Yuan; Ku, May Mei‐Sheng; Wu, Wendy Yi‐Ying; et al. (Cancer, 2020)
Background It is of paramount importance to evaluate the impact of participation in organized mammography service screening independently from changes in breast cancer treatment. This can be done by measuring the incidence of fatal breast cancer, which is based on the date of diagnosis and not on the date of death. Methods Among 549,091 women, covering approximately 30% of the Swedish screening‐eligible population, the authors calculated the incidence rates of 2473 breast cancers that were fatal within 10 years after diagnosis and the incidence rates of 9737 advanced breast cancers. Data regarding each breast cancer diagnosis and the cause and date of death of each breast cancer case were gathered from national Swedish registries. Tumor characteristics were collected from regional cancer centers. Aggregated data concerning invitation and participation were provided by Sectra Medical Systems AB. Incidence rates were analyzed using Poisson regression. Results Women who participated in mammography screening had a statistically significant 41% reduction in their risk of dying of breast cancer within 10 years (relative risk, 0.59; 95% CI, 0.51‐0.68 [P < .001]) and a 25% reduction in the rate of advanced breast cancers (relative risk, 0.75; 95% CI, 0.66‐0.84 [P < .001]). Conclusions Substantial reductions in the incidence rate of breast cancers that were fatal within 10 years after diagnosis and in the advanced breast cancer rate were found in this contemporaneous comparison of women participating versus those not participating in screening. These benefits appeared to be independent of recent changes in treatment regimens. Substantial and significant reductions in the incidence rates of fatal breast cancer and advanced breast cancer with 10 years of follow‐up are observed in this analysis of greater than one‐half million Swedish women participating and not participating in breast cancer screening. These comparisons are contemporaneous, and thus are not influenced by changes in therapeutic regimens.